(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
This study examines biodiversity credits in the context of the Kunming-Montreal Global Framework, drawing critical parallels with carbon markets and anticipating the implementation challenges that will be debated at COP-30. (Received: October 2025 | Accepted: November 2025)